Analysis of The Success of My Pelindo Application at PT Pelabuhan Indonesia III Based on DeLone and McLean ISSM - Muhammad Mashuri; Raihana Assa`'adah (Department of Statistics ITS, 2026)
As an organization with an important role in the port sector, PT Pelabuhan Indonesia has implemented information technology to support activities in all company sectors. In 2017, PT Pelindo launched an integrated application called My Pelindo, which serves employee administration needs. Since its launch, no evaluation has been conducted on the use of My Pelindo, especially at PT Pelindo III. Therefore, an evaluation is needed to measure user acceptance of the application. Currently, several methods exist to evaluate the success of information technology use, such as the Technology Acceptance Model (TAM), the Unified Theory of Acceptance and Use of Technology (UTAUT), and the DeLone and McLean Information System Success Model (D&M ISSM). Since the use of My Pelindo is mandatory and no alternative applications are available for comparison, the D&M ISSM was chosen to measure the success of My Pelindo from the users' perspective. Data was collected via surveys using questionnaires distributed to employees of PT Pelindo III Sub Region Java who use the application. The questionnaire was designed based on the six variables of the D&M ISSM: Information Quality, System Quality, Service Quality, Intention to Use, User Satisfaction, and Net Benefits. The survey data were analyzed using Partial Least Squares-Structural Equation Modeling (PLS-SEM) to identify relationships among variables and factors influencing the success of My Pelindo. The results showed that all indicators were valid, reliable, and significant in measuring their respective latent variables. It was found that Information Quality affects Intention to Use and User Satisfaction, while User Satisfaction and Intention to Use influence Net Benefits. Additionally, Net Benefits impact both Intention to Use and User Satisfaction.